Contribution of NOTCH1 genetic variants to bicuspid aortic valve and other congenital lesions. Issue 14 (14th March 2022) - Debiec, Radoslaw Marek; Hamby, Stephen E; Jones, Peter D; Safwan, Kassem; Sosin, Michael; Hetherington, Simon Lee; Sprigings, David; Sharman, David; Lee, Kelvin; Salahshouri, Pegah; Wheeldon, Nigel; Chukwuemeka, Andrew; et al.
Abstract : Introduction: Bicuspid aortic valve (BAV) affects 1% of the general population. NOTCH1 was the first gene associated with BAV. The proportion of familial and sporadic BAV disease attributed to NOTCH1 mutations has not been estimated. Aim: The aim of our study was to provide an estimate of familial and sporadic BAV disease attributable to NOTCH1 mutations. Methods: The population of our study consisted of participants of the University of Leicester Bicuspid aoRtic vAlVe gEnetic research—8 pedigrees with multiple affected family members and 381 sporadic patients. All subjects underwent NOTCH1 sequencing. A systematic literature search was performed in the NCBI PubMed database to identify publications reporting NOTCH1 sequencing in context of congenital heart disease. Results: NOTCH1 sequencing in 36 subjects from 8 pedigrees identified one variant c.873C>G/p.Tyr291* meeting the American College of Medical Genetics and Genomics criteria for pathogenicity. No pathogenic or likely pathogenic NOTCH1 variants were identified in 381 sporadic patients. Literature review identified 64 relevant publication reporting NOTCH1 sequencing in 528 pedigrees and 9449 sporadic subjects. After excluding families with syndromic disease pathogenic and likely pathogenic NOTCH1 variants were detected in 9/435 (2.1%; 95% CI: 0.7% to 3.4%) of pedigrees and between 0.05% (95% CI: 0.005% to 0.10%) and 0.08% (95% CI: 0.02% to 0.13%) of sporadic patients. Incomplete penetrance of definitely pathogenic NOTCH1 mutations was observed in almost half of reported pedigrees. Conclusions: Pathogenic and likely pathogenic NOTCH1 genetic variants explain 2% of familial and <0.1% of sporadic BAV disease and are more likely to associate with tetralogy of Fallot and hypoplastic left heart.